1990
DOI: 10.1136/bmj.301.6751.513
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of gastric cancer.

Abstract: Objective-To see whether investigation of dyspeptic patients aged over 40 after their first consultation with the general practitioner would increase the proportions with early and operable gastric cancers.Design-Prospective study of gastric cancer in dyspeptic patients aged over 40 from a defined population. Conclusions-The investigation of dyspeptic patients over 40 at first attendance can increase the proportion of early gastric cancers detected to 26% and the proportion of operable cases to 63%. Such a pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0
5

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(74 citation statements)
references
References 21 publications
3
66
0
5
Order By: Relevance
“…This is reflected in a 5-year survival as high as 90% for early gastric cancer [18]. Hallissey et al [19] have shown that the effective use of open access gastroscopy in Britain can achieve similar results, with the caveat that such outcomes depend largely on the awareness and effective use of this service by general practitioners. Nevertheless, despite the widespread introduction of open access gastroscopy in Britain, as many as one in three patients continue to present with advanced incurable cancers [4].…”
Section: Discussionmentioning
confidence: 83%
“…This is reflected in a 5-year survival as high as 90% for early gastric cancer [18]. Hallissey et al [19] have shown that the effective use of open access gastroscopy in Britain can achieve similar results, with the caveat that such outcomes depend largely on the awareness and effective use of this service by general practitioners. Nevertheless, despite the widespread introduction of open access gastroscopy in Britain, as many as one in three patients continue to present with advanced incurable cancers [4].…”
Section: Discussionmentioning
confidence: 83%
“…Seventeen identified factors that increased delay and six identified factors that decreased delay (Table 1). Delay in referral was primarily related to initial misdiagnosis of a common symptom or failure to make a diagnosis at the initial encounter with the patient (Bedikan et al, 1979;Nagao and Takahashi, 1979;Ojala et al, 1982;Hallissey et al, 1990;Arvanitakis et al, 1992;Rothwell et al, 1997). Moreover, referral was likely to be delayed if the patient was being treated for a benign condition, particularly with acid suppression (Mikulin and Hardcastle, 1987;Rothwell et al, 1997;Bramble et al, 2000).…”
Section: Factors Influencing Practitioner Delaymentioning
confidence: 99%
“…Se ha descrito también, un incremento progresivo en la frecuencia del tipo difuso según Laurén llegando en algunos países a superar al tipo intestinal, esto último en estrecha relación con la localización tumoral, reportándose actualmente una mayor frecuencia de tumores ubicados en el tercio superior y cardial; condición descrita como esperable en países desarrollados mientras que tumores de tercio inferior son más frecuentes en países en vías de desarrollo 7,9,[10][11][12][13] . Del mismo modo, se ha descrito un aumento gradual en el diagnóstico de lesiones incipientes a través de los años con el consiguiente impacto en la supervivencia de estos pacientes, condición determinada principalmente por los programas de detección precoz instaurados en Japón, China y Corea; el mejoramiento tecnológico de equipos; y la capacitación continua de endoscopistas y patólogos [14][15][16][17] . Los cambios descritos estarían influenciados por múltiples factores entre los que se mencionan modificación de hábitos alimentarios con aumento en el consumo de vegetales y menor consumo de carnes y productos salados; uso masivo de la refrigeración de alimentos e implementación de tratamientos altamente efectivos en la erradicación del Helicobacter pylori 10,11,[18][19][20][21][22][23] .…”
Section: Introductionunclassified